Pengaruh Penerapan Model Pembelajaran Inquiry Terhadap Kemampuan Berpikir Kritis Siswa Kelas IV SDN Sukamulya 05 - Gita Dwi Tamara Apriliyanti; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the application of the inquiry learning model on the critical thinking skills of fourth-grade students at SDN Sukamulya 05. The research method used was quantitative with a quasi-experimental design with a non-equivalent control group design. The subjects of the study were all fourth-grade students at SDN Sukamulya 05 in the 2024/2025 academic year, consisting of 28 students from the experimental class and 31 students from the control class. The research instrument was a pretest and posttest essay test referring to the Ennis critical thinking ability indicator. The analysis results showed that the average posttest score for the experimental class was 71.86, while the control class was 50.81. The independent t-test produced a tcount value = 8.66 with a significance of 0.000 <0.05, which means there is a significant difference between the two groups. Thus, the application of the inquiry learning model has a positive effect on improving students' critical thinking skills. The inquiry learning model can be an effective alternative learning strategy to improve critical thinking skills in elementary schools.